Door-to-Door COVID-19 Health Socialization and Herbal Immune Support in a Rural Village - Vikto Agus Wibowo; Happy Komikesari (Penerbit Goodwood, 2025)
Purpose: This study documents and evaluates a door-to-door community health socialization program on coronavirus disease 2019 knowledge and prevention delivered to households in Hadi Mulyo Village, Way Serdang Subdistrict, Mesuji Regency, with particular attention to elderly residents and the introduction of a locally prepared herbal immune support preparation. Methodology: A qualitative service learning design combined direct household visits organized across four residential blocks over a two-week period with structured observation, attendance registration, and informal interview data collected during each visit. Results: Thirty households across four blocks received individualized in home education covering virus biology, transmission, and prevention, after which residents demonstrated improved recognition of correct mask use, installed household handwashing stations where these had lapsed, and reported new awareness of ginger turmeric herbal preparations as a complementary immune-supportive practice. Conclusions: Household level, door to door health socialization is a feasible and well-received strategy for reinforcing pandemic preventive behavior in a rural village setting, particularly for elderly residents who are otherwise difficult to reach through group-based outreach during periods of restricted gathering. Limitations: The evaluation relied on a small, non-randomly selected number of households, a single outreach period, and qualitative observation rather than a validated quantitative instrument or comparison group. Contributions: This study contributes a replicable household level outreach model combining biomedical prevention and local herbal practices, offering guidance for community service programs targeting elderly and hard-to-reach populations in rural outbreaks.